2014
DOI: 10.1002/2014jc010188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ocean acidification on the biogenic composition of the sea-surface microlayer: Results from a mesocosm study

Abstract: The sea-surface microlayer (SML) is the ocean's uppermost boundary to the atmosphere and in control of climate relevant processes like gas exchange and emission of marine primary organic aerosols (POA). The SML represents a complex surface film including organic components like polysaccharides, proteins, and marine gel particles, and harbors diverse microbial communities. Despite the potential relevance of the SML in ocean-atmosphere interactions, still little is known about its structural characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 59 publications
(114 reference statements)
3
27
0
Order By: Relevance
“…During this study, the SML was sampled with the glass plate at ∼ 20 cm s −1 , yielding a thickness between 45 and 60 µm, with an overall mean value of 49 ± 8.89 µm (n = 39). This value is in good accordance with the proposed apparent sampling thickness of 50 ± 10 µm (Zhang et al, 1998) and fits well to previous observations for the SML sampled with a glass plate at the same withdrawal rate (Cunliffe et al, 2011; Galgani and Engel, 2013;Galgani et al, 2014;Zhang et al, 1998;Zhang, 2003). Using direct pH microelectrode measurements, Zhang (2003) later confirmed an in situ thickness of ∼ 60 µm for the SML, which they defined as the layer of sudden change of physico-chemical properties.…”
Section: Sml Properties and Organic Matter Accumulationsupporting
confidence: 92%
See 2 more Smart Citations
“…During this study, the SML was sampled with the glass plate at ∼ 20 cm s −1 , yielding a thickness between 45 and 60 µm, with an overall mean value of 49 ± 8.89 µm (n = 39). This value is in good accordance with the proposed apparent sampling thickness of 50 ± 10 µm (Zhang et al, 1998) and fits well to previous observations for the SML sampled with a glass plate at the same withdrawal rate (Cunliffe et al, 2011; Galgani and Engel, 2013;Galgani et al, 2014;Zhang et al, 1998;Zhang, 2003). Using direct pH microelectrode measurements, Zhang (2003) later confirmed an in situ thickness of ∼ 60 µm for the SML, which they defined as the layer of sudden change of physico-chemical properties.…”
Section: Sml Properties and Organic Matter Accumulationsupporting
confidence: 92%
“…Significant correlations between organic matter concentration in the SML and in the ULW were determined and showed that the SML basically reflects the underlying seawater system. The close connectivity between SML organic properties and biological development was also shown during a recent meso- cosm study, indicating that ecosystem changes impact SML organic matter composition and concentration (Galgani et al, 2014). Despite this finding that relates to a more general characteristic of the SML, clear differences in the accumulation behavior of different organic matter components were determined during this study and are in good accordance with previous observations.…”
Section: Organic Matter Characteristics Of the Sml In The Upwelling Rsupporting
confidence: 91%
See 1 more Smart Citation
“…chla concentrations, total prokaryotic cells and virus-like particles abundances), there were no strong discernible differences between the control, C3, or the acidified mesocosms, P3 and P6, along the course of the experiments; however, there were often large differences between the two campaigns due to the pre-bloom and non-bloom conditions. While several studies have shown the effects of ocean acidification on biogeochemical parameters in eutrophic waters (Galgani et al, 2014;Schulz et al, 2013), observations from the MedSea experiment showed no effect of ocean acidification on most of the biogeochemical parameters in these oligo-to mesotrophic areas. These results are discussed more fully in Gazeau et al (2015).…”
Section: Resultsmentioning
confidence: 75%
“…This modified organic "skin" has the potential to influence the flux of gases across the air-water interface [51]. As the biological response to ocean change affects the SML compounds and processes [10,13,[52][53][54], we expect that plastic pollution will have tangible effects on SML composition and reactivity as well.…”
Section: Plastic Accumulation and Other Pollutants In The Sea Surfacementioning
confidence: 99%